Salicylic Acid Biosynthesis in Plants - Lefevere, Hannes; Bauters, Lander; Gheysen, Godelieve (Frontiers in Plant Science, 2020)
Salicylic acid (SA) is an important plant hormone that is best known for mediating host responses upon pathogen infection. Its role in plant defense activation is well established, but its biosynthesis in plants is not fully understood. SA is considered to be derived from 2 possible pathways; the ICS and PAL pathway both starting from chorismate. The importance of both pathways for biosynthesis differs between plant species, rendering it hard to make generalizations about SA production that cover the entire plant kingdom. Yet, understanding SA biosynthesis is important to gain insight into how plant pathogen responses function and how pathogens can interfere with them. In this review we take a closer look at how SA is synthesized and the importance of both biosynthesis pathways in different plant species.